2013
DOI: 10.4236/ajibm.2013.37069
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Prevalent Destructive Leadership Behaviour on Subordinate Employees in a Firm

Abstract: This paper examines the impact of destructive leadership behaviours experienced by subordinate employees. Structured questionnaires based on the petty Tyranny in organizations scale to explore the scope and nature of destructive leadership were used. The study further explores the relationship among leadership experiences, various measures of subordinates' satisfaction and turnover level. The results showed that despite the central role of leadership holds for many firms in Hanoi, Vietnam, subordinate employee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…These behaviors are therefore called destructive leadership behavior because they destabilize or sabotage the well-being, motivation, and satisfaction of employees, as well as target the efficiency of organizational tasks, resources, and goals (Schyns & Schilling, 2013). It has been shown that these types of leader behaviors often alienate the followers who employ passive and aggressive behaviors as a response, which can result in retaliation from the leader or the followers (Yen, Tian, & Sankoh, 2013). Based on the increased incidence of behaviors that create often times hostile work environments, the U.S.…”
Section: Forms Of Ineffective Leadership Related To Occupational Stressmentioning
confidence: 99%
See 1 more Smart Citation
“…These behaviors are therefore called destructive leadership behavior because they destabilize or sabotage the well-being, motivation, and satisfaction of employees, as well as target the efficiency of organizational tasks, resources, and goals (Schyns & Schilling, 2013). It has been shown that these types of leader behaviors often alienate the followers who employ passive and aggressive behaviors as a response, which can result in retaliation from the leader or the followers (Yen, Tian, & Sankoh, 2013). Based on the increased incidence of behaviors that create often times hostile work environments, the U.S.…”
Section: Forms Of Ineffective Leadership Related To Occupational Stressmentioning
confidence: 99%
“…Inhibitory leader behaviors are called destructive leadership behavior because they destabilize or sabotage the well-being, motivation, and satisfaction of employees, as well as target the efficiency of organizational tasks, resources, and goals (Schyns & Schilling, 2013). It has been shown that these types of leader behaviors often alienate the followers who employ passive and aggressive behaviors as a response, which can result in retaliation from the leader or the followers (Yen et al, 2013). The effects of ineffective leadership on followers were consistent with a previous finding, which found feelings of depression, belittlement, humiliation, and a sense of meaninglessness about their role in an organization (Pelletier, 2010) with the followers.…”
Section: Rq2: What Are the Lived Experiences Of Occupational Stress mentioning
confidence: 99%
“…The JV Lead management as awhole-project lead entity appears to think that it has the right and duty to operate in the way that they do with clear indications of misplaced confidence, poor judgement and the absence of quality practices (Furnham, 2010) -presupposing a selective interpretation of reality (Mumford et al,2007)by acting as a corporate psychopath (Boddy, Ladyshewsky and Galvin, 2010).The JV Lead management entity also appears to think that it can violate organisational legitimacy and rules (Yen, Tian, and Sankoh, 2013) through overt subterfuge and sabotage whilst ignoring staff requirements (Flynn, 1999), their well-being (Einarsen, Aasland and Skogstad, 2007;Reed, 2004) and also legal and ethical obligations (corporate restrictions through international group oversight processes and contractual and other compliance requirements).…”
Section: How the Jv Lead Management Thinks As A Toxic Leadermentioning
confidence: 99%